2020
DOI: 10.1093/cid/ciaa1870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospitalization Incidence in Influenza Outpatients Treated With Baloxavir Marboxil or Neuraminidase Inhibitors: A Health Insurance Claims Database Study

Abstract: Background Baloxavir marboxil (baloxavir) is a single-dose, oral anti-influenza drug with a novel mechanism of action. We compared the incidence of hospitalization in patients treated with baloxavir versus neuraminidase inhibitors. Methods This was a retrospective observational cohort study using real-world patient data extracted from a Japanese health insurance claims database. The enrollment period was October 1, 2018 to Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Real-world data comparing baloxavir and three NAIs (oseltamivir, zanamivir, and laninamivir) suggested that baloxavir users had a lower incidence of hospitalization compared with oseltamivir and zanamivir users in the outpatient setting. NAI users had more need for additional anti-influenza drug use than baloxavir users [69 ▪ ]. A network meta-analysis confirmed the clinical efficacy of all four NAIs and baloxavir with a shortening of time to alleviate influenza symptoms (TTAS), with zanamivir associated with the shortest TTAS.…”
Section: Endonuclease Inhibitormentioning
confidence: 89%
“…Real-world data comparing baloxavir and three NAIs (oseltamivir, zanamivir, and laninamivir) suggested that baloxavir users had a lower incidence of hospitalization compared with oseltamivir and zanamivir users in the outpatient setting. NAI users had more need for additional anti-influenza drug use than baloxavir users [69 ▪ ]. A network meta-analysis confirmed the clinical efficacy of all four NAIs and baloxavir with a shortening of time to alleviate influenza symptoms (TTAS), with zanamivir associated with the shortest TTAS.…”
Section: Endonuclease Inhibitormentioning
confidence: 89%
“…We included repetitive cases of influenza in 1 season as an independent variable in the multivariable analyses to assess whether repetitive influenza increases the risk of bacterial pneumonia. Furthermore, anti-influenza drugs have been reported to suppress SP development, depending on the type of drug used [ 25 ]. Therefore, the types of anti-influenza drugs were also included as possible confounding factors in the multivariable regression model for SP.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to placebo, baloxavir significantly improved time to improvement [23 ▪▪ ] and time to alleviation [21] of influenza symptoms; and faster viral clearance for adults compared with placebo or oseltamvir [21]. Observational data in Japan have shown decreased hospitalizations for patients treated with baloxavir vs oseltamivir [26]. Although neuraminidase inhibitors tend to be less efficacious for influenza B, baloxavir was observed to have superior clinical efficacy in time to improvement in influenza symptoms compared to both placebo and oseltamivir [23 ▪▪ ,27].…”
Section: Influenza Therapeuticsmentioning
confidence: 96%